Cost effectiveness of a practice-based intervention to improve vaccination rates in adults less than 65-years-old - Kenneth J. Smith; Mary Patricia Nowalk; Chyongchiou J. Lin; Richard K. Zimmerman (Taylor & Francis Group, 2017)
The cost-effectiveness of the 4 Pillars™ Practice Transformation Program to improve vaccination rates in adults <65-years-old is unknown. Two vaccines, influenza and Tdap (tetanus, diphtheria, acellular pertussis), were targeted for this age group. Cost-effectiveness of the intervention compared with control, with a primary outcome of cost per quality adjusted life year (QALY) gained, was estimated from societal and third party payer perspectives over a 10-year time horizon using a decision analysis model. Vaccination rates and intervention costs were derived from an intervention trial, and vaccine effectiveness, illness rates, and costs with/without vaccination were obtained from US databases and literature data. Future costs and effectiveness were discounted at 3%/year. The intervention cost was $1.78 per eligible patient/year. From the societal perspective, per patient total vaccination and illness costs with the intervention were $27.43 higher than control while gaining 0.00087 QALYs, costing $31,700/QALY gained. The intervention, extrapolated to the US population, could prevent 4.2 million cases, 87,489 hospitalizations, and 5,680 deaths due to influenza over 10 y in adults <65-years-old. In a probabilistic sensitivity analysis, the intervention was favored in 68.2% of model runs at a $50,000/QALY level and in 94.3% at $100,000/QALY. In a separate scenario analysis, the intervention became cost saving if influenza economic burden was >$2,099 per case (societal base case $846). Thus, the 4 Pillars Practice Transformation Program is an economically reasonable intervention to improve vaccination rates in adults <65-years-old, and could have a substantial public health impact.